The Preferred Management of a Single-Digit Distal Phalanx Amputation - Kwon, Soo-Ha; Lao, William Wei-Kai; Hsu, Angela Ting-Wei; Lee, Che-Hsiung; Hsu, Chung-Chen; Huang, Jung-Ju; Qiu, Shan Shan; Tilkorn, Daniel; Tang, Evelyn Ting-Hsuan; Lu, Johnny Chuieng-Yi; Chang, Tommy Nai-Jen (Journal of Reconstructive Microsurgery, 2020)
Background Replantation of a single digit at the distal phalanx level is not routinely performed since it is technically challenging with questionable cost-effectiveness. The purpose of this study was to analyze international microsurgeons' clinical decisions when faced with this common scenario.Methods A survey of a right-middle finger distal phalanx transverse complete amputation case was conducted via online and paper questionnaires. Microsurgeons around the world were invited to provide their treatment recommendations. In total, 383 microsurgeons replied, and their responses were stratified and analyzed by geographical areas, specialties, microsurgery fellowship training, and clinical experiences.Results Among 383 microsurgeons, 170 (44.3%) chose replantation as their preferred management option, 137 (35.8%) chose revision amputation, 62 (16.2%) chose local flap coverage, 8 (2.1%) chose composite graft, and 6 (1.6%) favored other choices as their reconstruction method for the case study. Microsurgeons from the Asia-Pacific, Middle East/South Asia, and Central/South America regions tend to perform replantation (70.7, 68.8, and 67.4%, respectively) whereas surgeons from North America and Europe showed a lower preference toward replantation (20.5 and 26.8%, respectively p < 0.001). Having completed a microsurgery fellowship increased the attempt rate of replantation by 15.3% (p = 0.004). Clinical experience and the surgeons' specialties did not show statistical significance in clinical decision making.Conclusion From the present study, the geographic preferences and microsurgery fellowship experience influence the method of reconstruction for distal phalanx amputation. Multiple factors are taken into consideration in selecting the most suitable reconstructive method for each case scenario. In addition to the technical challenges of the proposed surgery, the cost of the procedure and the type of facility needed are important variables in the decision making process.
Keywords: distal phalanx reconstruction; replantation; questionnaire